Analisis Rasio Laporan Keuangan dalam Mengukur Kinerja Perusahaan PT. Kalbe Farma Tbk Tahun 2018-2021 - Fernadi Abi Wijaya; Lovinza Lovinza; Ratih Kusumastuti (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of the study was to specify the increase in financial performance for the pandemic in pharmaceutical division. PT. Kalbe Farma Tbk registed on Indonesian Stock Exchange (IDX). The approach method used is the quantitative descriptive approach. The species of data used is secondary data facile from the Indonesia Stock Exchange, ie financial statements of PT. Kalbe Farma Tbk from 2018 to 2021. The ratio analysis used in this study includes analysis of liquidity, solvency, activity and profitability ratios. As a result, the liquidity and solvency ratios over the past four years have been in good shape for the company as it has been competent to meet all its obligations, but the profitability and activity ratios have fluctuated and are trending downward. It was shown that there was Researchers say PT. Kalbe Farma Tbk uses ratio analysis to measure financial performance, and the results generally increase percentages, but not significantly.